Effect of combined oral contraceptive use on serum 25-hydroxy vitamin D levels and ultrasound parameters in patients with polycystic ovary syndrome. (2nd April 2016) - Namli Kalem, Müberra; Hizli, Deniz; Kamalak, Zeynep; Kösüs, Aydin; Kösüs, Nermin; Turhan, Nilgün; Kafali, Hasan
Abstract: Purpose : To investigate if there is an effect of combined oral contraceptive (COC) use on serum 25-hydroxy vitamin D [25(OH)D] levels in patients with polycystic ovary syndrome (PCOS). Methods : PCOS was defined by the 2003 Rotterdam criteria. All patients with PCOS were treated with a COC containing 0.035 mg ethinylestradiol and 2 mg cyproterone acetate for 6 months. Serum 25(OH)D levels, HOMA–IR, ovarian volume and antral follicule count were measured before and after the treatment. Results : The median 25(OH)D levels were 9.40 (range 4.40–24.50) μg/l and 7.00 (5.00–13.50) μg/l before and after COC use, respectively. Serum 25(OH)D levels decreased after the treatment; however, the difference was not statistically significant ( p  = 0.055). Conclusion : This study seems to be the first prospective trial revealing the effect of COC use on serum 25(OH)D levels in women with PCOS. Although the decrease in serum 25(OH)D levels in patients with PCOS with the use of COC alone, did not reach to statistically significance level after 6 months treatment with COC.